Writing Skills Needed for the Communication Industry - Melyssa Savoia (International Journal of Educational Technology and Artificial Intelligence, 2022)
This descriptive study aims to determine what competencies are most needed by employers of undergraduate fields of study in Communication Science to meet the profession’s needs. The method used in this research is a descriptive method, with a collection of data that originates from the ads required by employers, then analysis to present the data in various categories. The results obtained are maps of professions and competencies most needed by employers. By knowing the required professional competence and employers, students can prepare themselves to develop competence and professionalism that is being developed in realizing the ideals and hopes. Likewise, for educational institutions, Communication Science can significantly adapt the curriculum to meet employers’ needs.